2002
DOI: 10.4049/jimmunol.169.4.1688
|View full text |Cite
|
Sign up to set email alerts
|

Mature Dendritic Cell Generation Promoted by Lysophosphatidylcholine

Abstract: During the acute phase response the interplay between high density lipoproteins and low density lipoproteins (LDL) favors transient generation of oxidized LDL with proinflammatory activities. We hypothesized that oxidative modification of LDL is an endogenous signal for the immune system and have shown that oxidized LDL promotes mature dendritic cell transition from monocyte therefore linking the non specific acute phase response to adaptive immunity. Lysophosphatidylcholine (LPC) is a major lipid component of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 51 publications
1
83
0
Order By: Relevance
“…Indeed, acute phase lipoproteins can be submitted to biochemical modifications that lead to the production of bioactive molecules. Among these molecules, LPC is known to be a pro-inflammatory lysophospholipid and to stimulate the generation of mature DC from differentiating monocytes in vitro [8]. This raised the Alum is associated with a Th2-oriented immune response characterized by a strong humoral response but a poor cellular immunity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, acute phase lipoproteins can be submitted to biochemical modifications that lead to the production of bioactive molecules. Among these molecules, LPC is known to be a pro-inflammatory lysophospholipid and to stimulate the generation of mature DC from differentiating monocytes in vitro [8]. This raised the Alum is associated with a Th2-oriented immune response characterized by a strong humoral response but a poor cellular immunity.…”
Section: Discussionmentioning
confidence: 99%
“…The following experiments were designed to explore the ability of LPC to prime Ag-specific In previous reports, we showed that the action of LPC on DC in vitro could be blocked by Intralipid (IL), a therapeutic lipid emulsion currently used for parenteral nutrition in case of septic shock [8]. Figure 1C shows that co-injection of IL with HEL+LPC strongly inhibited the induction of the HEL-specific T cell response, indicating that IL can antagonize in vivo the immunostimulating effect of LPC.…”
Section: Lpc Primes Specific T Cell Responses In Vivomentioning
confidence: 99%
See 3 more Smart Citations